2012
DOI: 10.1016/s2221-1691(12)60083-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of artemether on hematological parameters of healthy and uninfected adult Wistar rats

Abstract: The results suggest that artemether can induce reversible changes in hematological profiles of rats by extension man. This can probably aggravate anemia when artemether is administered to malaria patients. Hence, the study supports the use of the drug with caution especially in patients prone to anemic tendencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 16 publications
1
18
2
Order By: Relevance
“…Several studies reported higher haemoglobin and RBC values (Ola-Davies et al 2014, Vinodini et al 2015, and lower WBC values (Osonuga et al 2012) in rats of Wistar strain than we found. Ashaolu et al (2011) determined similar results to ours for RBC counts in the blood of Wistar rats.…”
Section: Discussioncontrasting
confidence: 56%
“…Several studies reported higher haemoglobin and RBC values (Ola-Davies et al 2014, Vinodini et al 2015, and lower WBC values (Osonuga et al 2012) in rats of Wistar strain than we found. Ashaolu et al (2011) determined similar results to ours for RBC counts in the blood of Wistar rats.…”
Section: Discussioncontrasting
confidence: 56%
“…This was done according to Osonuga, et al [30] and Aprioku, 2012 [31]. Dosage was calculated with reference to the dose of artemether in the drug combination.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, antimalarial agents have been reported to aggravate anaemia in malaria cases. Osonuya et al, [12], reported that artemether can aggravate anaemia when administered in malaria infection. The study reported decrease in red blood cell count, haemoglobin concentration and white blood cell count in albino rats.…”
Section: Discussionmentioning
confidence: 99%